La aplicación de la ley de consulta previa a los pueblos indígenas u originarios N° 29785, vulneraría el derecho a la libre determinación de los pueblos en el perú - Ocupa Abad, Elia Yocsune (2016)
The present research is to describe and analyze the position of the State with respect to indigenous communities in Peru, as it is an important step in the process of social inclusion that the current government has proposed as reform plan Factor government, and for that he has used legislative proposals on granting the right to consultation as in Latin American countries that already have such a law. Thus, the legislature enacted Law No. 29785 Prior Consultation Law and its regulations DS No. 001-2012 -MC, which should be implemented in coordination with indigenous peoples to reach a mutual agreement to benefit not only the state but the same. But the state in an effort to attract private investment, especially foreign, which has failed to implement it, ignoring the law and therefore indigenous peoples. For the present study, we analyzed the Prior Consultation Law No. 29785, checking for that international and national regulations and the jurisprudence of the Constitutional Court. It has also carried out an analysis of the right to enjoy an adequate and balanced development of life environment, up to the current state of the right to prior consultation in Peru, and demonstrate the shortcomings in the implementation of the Law Consultation previous No. 29785 to guarantee the right of indigenous peoples to prior consultation, linked to the principle of self-determination of peoples, employing, hermeneutical, analytical, historical methods, among others